MENINGKATKAN KOMPETENSI GURU MATEMATIKA DI SEKOLAH BINAAN MELALUI SACC - Aan Andryani (Jurnal Ilmu dan Budaya, 2018)
The teachers must prepare a good planning ,so that they could improve the learning process.The planning are include choosing and using the method and the media which are relevant with the standard competence or basic competence to achieve the learning outcomes..In fact,the real condition of the math teacher in the scool target,such as SMPN 7, SMPN 10, SMP Muhmmadiyah 5,SMP PGRI 5,SMP Kartika XIX, SMP Plus Darussurur, and SMP Kreatif Harapan Bangsa are less of creativity.That is why the result is not as expected as the target.Though the SACC, which the supervisor used by visiting the School target several times. It found the satisfy result.From the lesson planning which was originally 22,87,improve into 26 in cycle II and 30,2 in cycle III.Futhermore,the teaching learning process which was orginally 55,80 improve into 62,30 in cycle II and 71,20 in cycle III.It can be concluded that the SACC method is successfully work.